LAW ENFORCEMENT BASED ON THE ENVIRONMENT: SOLUTION OF LAND PROBLEMS AFTER TSUNAMI, LIQUEFACTION, AND EARTHQUAKE IN CENTRAL SULAWESI - Sulbadana Sulbadana (Diponegoro Law Review, 2020)
On September 28, 2018, there was a natural disaster in the form of Tsunami, Liquefaction, and Earthquake that struck Palu City. Sigi Regency and Donggala Regency, Central Sulawesi Province, in addition to damaging various infrastructures, the natural disaster also claimed lives that made the government have to issue a policy by setting red zones or areas that are not habitable. With the policy to determine the red zone, it will certainly cause problems related to the status of the land after being abandoned by the owner and until now there is no certainty related to what is the basis for the determination of the red zone by the government, there is no guarantee that the red zone is an uninhabitable area, giving rise to a polemic what if after being abandoned for a long time it turns out that nothing happened as feared in the red zone. The law is demanded to be present to answer the problem and provide solutions for all parties with a legal approach based on ecology and the values of natural balance.